1987
DOI: 10.2136/sssaj1987.03615995005100050013x
|View full text |Cite
|
Sign up to set email alerts
|

Selenite Adsorption on Alluvial Soils: II. Solution Composition Effects

Abstract: The adsorption envelope for selenite on two alluvial soils from the San Joaquin Valley, California, was investigated with respect to variations in solution composition. Sodium‐saturated soil pastes were mixed with solutions containing sulfate, phosphate, and Ca ions in a background electrolyte of 50 mol NaCl m−3. The effects of increasing chloride concentration were investigated at 100 mol NaCl m−3. No discernible change in the amount of selenite adsorbed was found as a result of increased chloride concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 0 publications
3
33
1
1
Order By: Relevance
“…3 it is clear that there exists a considerable percentage of adsorption above the value of pH pzc , i.e., the pH at which the adsorbent surface is negatively charged. This indicates that the adsorption is not only due to the electrostatic force of attraction between the adsorbent surface and SeO 2− 3 ion but also due to a combined effect of both chemical, i.e., ligand exchange type (26), and electrostatic interaction. Further, in order to prove an ion exchange mechanism, the XRD of one selenite exchanged sample was taken, and a shift in the peak position (003 line) toward lower 2θ values compared to the parent hydrotalcite was observed.…”
Section: Ph-dependent Adsorptionmentioning
confidence: 99%
“…3 it is clear that there exists a considerable percentage of adsorption above the value of pH pzc , i.e., the pH at which the adsorbent surface is negatively charged. This indicates that the adsorption is not only due to the electrostatic force of attraction between the adsorbent surface and SeO 2− 3 ion but also due to a combined effect of both chemical, i.e., ligand exchange type (26), and electrostatic interaction. Further, in order to prove an ion exchange mechanism, the XRD of one selenite exchanged sample was taken, and a shift in the peak position (003 line) toward lower 2θ values compared to the parent hydrotalcite was observed.…”
Section: Ph-dependent Adsorptionmentioning
confidence: 99%
“…Fe and Mn oxides) (BALISTRIERI and CHAO, 1990;HAYES et al, 1989). Earlier investigations suggested that Se(IV) behaves like phosphate, forming strong inner-sphere sorption complexes (BARROW and WHELAN, 1989;NEAL et al, 1987a;NEAL et al, 1987b;ZHANG and SPARKS, 1990) and substituting for phosphate in apatite (DUC et al, 2003;MONTEIL-RIVERA et al, 2000).…”
Section: Speciation Of Selenium In Reductive Environmentsmentioning
confidence: 99%
“…Dissolution and leaching of soil salts by irrigation water is a primary source of selenium to shallow groundwater in the western San Joaquin Valley. The following references present a very detailed geochemical understanding of selenium that is transferable to most environments: Fio and Fujii (1990), Fio et al (1991), Neal et al (1987aNeal et al ( , 1987b, Neal and Sposito (1989), Sposito et al (1988), Sposito et al (1991), andWright (1999). Within these references sorption studies showed that selenate is not adsorbed to the alluvial fan soils, whereas selenite is rapidly adsorbed.…”
Section: 26mentioning
confidence: 99%